Spread of tau down neural circuits precedes synapse and neuronal loss in the rTgTauEC mouse model of early Alzheimer's disease. Issue 6 (6th March 2017) - Pickett, Eleanor K.; Henstridge, Christopher M.; Allison, Elizabeth; Pitstick, Rose; Pooler, Amy; Wegmann, Susanne; Carlson, George; Hyman, Bradley T.; Spires‐Jones, Tara L.
Abstract: Synaptic dysfunction and loss is the strongest pathological correlate of cognitive decline in Alzheimer's disease (AD) with increasing evidence implicating neuropathological tau protein in this process. Despite the knowledge that tau spreads through defined synaptic circuits, it is currently unknown whether synapse loss occurs before the accumulation of tau or as a consequence. To address this, we have used array tomography to examine an rTgTauEC mouse model expressing a P301L human tau transgene and a transgene labeling cytoplasm red (tdTomato) and presynaptic terminals green (Synaptophysin‐EGFP). All transgenes are restricted primarily to the entorhinal cortex using the neuropsin promotor to drive tTA expression. It has previously been shown that rTgTauEC mice exhibit neuronal loss in the entorhinal cortex and synapse density loss in the middle molecular layer (MML) of the dentate gyrus at 24 months of age. Here, we observed the density of tau‐expressing and total presynapses, and the spread of tau into the postsynapse in the MML of 3–6, 9, and 18 month old red–green‐rTgTauEC mice. We observe no loss of synapse density in the MML up to 18 months even in axons expressing tau. Despite the maintenance of synapse density, we see spread of human tau from presynaptic terminals to postsynaptic compartments in the MML at very early ages, indicating that the spread of tau through neural circuits is not due to the degeneration of axon terminals and is an early feature of the disease process. Abstract : Pickett et al. show using high‐resolution array tomography imaging (top) that tau protein (blue) spreads from presynaptic terminals (green) of entorhinal cortex neurons (EC) to postsynaptic terminals (red) in the middle molecular layer of the dentate gyrus (DG) of the hippocampus (bottom) before substantial synapse loss occurs. This demonstrates that presynaptic terminal degeneration is not necessary for tau to spread through neural circuits.